Prospective assessment of circulating tumor DNA in patients with metastatic uveal melanoma treated with tebentafusp - Manuel Rodrigues; Toulsie Ramtohul; Aurore Rampanou; José Luis Sandoval; Alexandre Houy; Vincent Servois; Léah Mailly-Giacchetti; Gaelle Pierron; Anne Vincent-Salomon; Nathalie Cassoux; Pascale Mariani; Caroline Dutriaux; et al. (Nature Communications)
Abstract Tebentafusp, a bispecific immune therapy, is the only drug that demonstrated an overall survival benefit in patients with metastatic uveal melanoma (MUM). Circulating tumor DNA (ctDNA) has emerged as a potential prognostic and predictive marker in the phase 3 IMCgp100-202 trial using multiplex PCR-based next-generation sequencing (NGS). In this study (NCT02866149), ctDNA dynamics were assessed using droplet digital PCR (ddPCR) in 69 MUM patients undergoing tebentafusp treatment. Notably, 61% of patients exhibited detectable ctDNA before treatment initiation, which was associated with shorter overall survival (median 12.9 months versus 40.5 months for patients with undetectable ctDNA; p < 0.001). Patients manifesting a 90% or greater reduction in ctDNA levels at 12 weeks demonstrated markedly prolonged overall survival (median 21.2 months versus 12.9 months; p = 0.02). Our findings highlight the potential of ddPCR-based ctDNA monitoring as an economical, pragmatic and informative approach in MUM management, offering valuable insights into treatment response and prognosis.